Surfacing and diving behavior associated with thermal physiology in oceanic habitats of skipjack tuna (Katsuwonus pelamis) in the western north Pacific Ocean - Aoki, Yoshinori; Kitagawa, Takashi; Kiyofuji, Hidetada (Frontiers in Physiology, 2025)
IntroductionThermal physiology is a pivotal biotic factor for the ecophysiology of commercially valuable tuna, influencing not only horizontal but also vertical behaviors. We aimed to examine how the thermal physiology of skipjack tuna (Katsuwonus pelamis, SKJ) can explain the differences in their vertical behavior, focusing on surfacing and diving, among various thermal environments during their northward migration in the western North Pacific.MethodsWe analyzed archival tag data collected during 2012–2015, with individual time series (Fork length: 38–49 cm, N = 38) of swimming depth, water temperature, and peritoneal body temperature during northward migration from subtropical areas to temperate regions around Japan. We quantified surfacing and diving behavior as an index of vertical behavior and estimated the whole-body heat transfer coefficient (λ) during the cooling and warming phases associated with diving using body and water temperature records as indicators of thermal physiology.ResultsIn the southern mixed layer areas, SKJ were widely distributed at a depth layer <200 m, whereas they were restricted to the surface in the strong thermocline areas in the north. The dive duration was significantly shortened with a strong thermal gradient during northward migration. We observed minor to no differences in λ values between the cooling and warming phases in the southern areas, whereas the λ values in temperate areas differed by a factor of 2–3 between the phases.DiscussionOur findings of changes in λ values between the cooling and warming phases represent the first evidence of thermoregulation in SKJ. Surfacing preference behavior and short dive duration in temperate areas may be an avoidance of prolonged exposure to cold temperatures, a behavior commonly exhibited in other tuna. Moreover, we discussed how the changes in vertical behavior driven by thermal physiology can explain spatial heterogeneity in SKJ fishery grounds in the western Pacific Ocean.